2003
DOI: 10.1063/1.1618368
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation in stacked InAs/GaAs quantum dots studied by Raman scattering

Abstract: We report a Raman scattering investigation of InAs vibrational modes in multiple layers of InAs self-assembled quantum dots in a GaAs matrix. The Raman peak associated with quantum-dot phonons shows a downward frequency shift as the interlayer spacing decreases. We attribute this frequency shift to the relaxation of the elastic strain in the stacked quantum-dot layers. From the phonon frequency shift, we estimate the magnitude of the strain in the quantum dot layers, which we relate to the energy of the photol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…We have recently shown that the strain in stacked QD structures can be probed by Raman scattering. 14 We found that the frequency of the QD phonon peak decreases as the spacing between QD layers is reduced in samples containing ten layers of InAs/ GaAs QDs. These frequency shifts were attributed to the strain relaxation that takes place during the growth of the QD multilayer system.…”
Section: Inas/ Gaas Stacked Qdsmentioning
confidence: 89%
See 4 more Smart Citations
“…We have recently shown that the strain in stacked QD structures can be probed by Raman scattering. 14 We found that the frequency of the QD phonon peak decreases as the spacing between QD layers is reduced in samples containing ten layers of InAs/ GaAs QDs. These frequency shifts were attributed to the strain relaxation that takes place during the growth of the QD multilayer system.…”
Section: Inas/ Gaas Stacked Qdsmentioning
confidence: 89%
“…This feature is assigned to the InAs LO-like QD phonon on the basis of its frequency position and selection rules. 13,14 The QD peak in the sample containing In 0.5 Ga 0.5 As QDs is clearly shifted to lower frequencies with respect to the peak that appears in the InAs QD sample. As discussed in Sec.…”
Section: A In X Ga 1−x As Qds Versus Inas Qdsmentioning
confidence: 99%
See 3 more Smart Citations